Two New Species of the Genus Lytocestus (Caryophyllidea- Lytocestidae) from Freshwater Catfish, Clarias Batrachus Linnaeus (1758) - C.J. Hiware*, R.T. Pawar and (Recent Research in Science and Technology, 2011)
The present paper deals with the two new caryophyllaeid species of the genus Lytocestus viz. L. vyasaei n.sp. and L. purnensis n.sp. from the freshwater catfish Clarias batrachus L. from Marathwada region (M.S.) India. The differentiating characters of L. vyasaei are long, neck absent, head is conical shape, and ovary is bilobed, butterfly shaped. In L. purnensis body is elongated, grass blade like, neck present, and ovary is bilobed, H – shaped each lobe joined each other by ovarian isthmus.